Speech Perception and The Role of Semantic Richness in Processing - Nenadic, Filip; Kelley, Matthew C.; Podlubny, Ryan G.; Tucker, Benjamin V. (Canadian Acoustics, 2019)
The richness of meaning associated with specific words has been found to influence word recognition. Such findings, however, have come largely from studies based on visual word recognition, and related studies focusing on the acoustic signal and speech perception are less common. The present work recognizes that any effects observed may vary across modalities, and explores semantic richness effects as they may pertain to the perception and processing of spoken language. Goh et al. (2016) describe an auditory lexical decision experiment where concreteness, valence, arousal, semantic neighborhood density, and semantic diversity are found to affect spoken word recognition. The stimuli used in their study were limited to a set of fewer than 500 words, most of which were concrete nouns. In our study, we expand the scope of the analysis to include 9,086 words taken from the Massive Auditory Lexical Decision database (MALD; Tucker et al., 2019), each with corresponding values for each of the semantic variables of interest. In complement to the results described by Goh and colleagues, generalized additive mixed modelling indicates significant effects of concreteness, valence, arousal, and semantic neighborhood density on response latency. No effect was observed for semantic diversity. These results suggest that the processing of acoustic signals is influenced by top down semantic effects, even in decontextualized environments. While the specifics of these effects differ by semantic variable, it appears that increased semantic richness facilitates spoken word recognition.